THE EFFECT OF BARANGAN BANANA (Musa sapientum L.) PEEL WASTE ON TOMATO (Lycopersicum esculentum MILL.) PLANT GROWTH - Fajriana, Nurul (Jurnal Biologi Sains dan Kependidikan, 2021)
Research on "The Effect of Barangan Banana peel Waste on Tomato Plant Growth" aims to determine the effect of giving barangan banana peel waste on the growth of tomato plants, and to determine how many doses of barangan banana peel waste can affect the growth of tomato plants. The method used was experimental design with a non-factorial randomized block design (RBD) with a combination of 5 treatments in 4 groups. Parameters measured were stem height, number of leaves, wet weight, and dry weight of tomato plants. Data analysis used ANOVA test followed by the least significant difference test and Duncan's test. The least significant difference test is only used on the height of the tomato stems 15 days after planting because the number of coefficient of diversity obtained is 20%. The results showed that the application of barangan banana peel waste to tomato plants had a significant effect on stem height, wet weight and dry weight, but did not significantly affect the number of leaves. The highest measurement results obtained from stem height, number of leaves, wet weight and dry weight at the age of 15 dast to 45 dst were P3 treatment by giving 1200 g / plot of banana peel waste and the lowest results for tomato stem height, number of leaves, wet weight and dry weight was obtained in treatment P0 (without giving banana peel waste). From the study results, it can be concluded that the application of barangan banana peel waste affects the growth of tomato plants.